Relationship Between Lactic Acid Level with Low Back Pain (LBP) on Taxi Drivers Pekanbaru - Yuharika Pratiwi; Siska Andriani Rukmana; Afriwardi Afriwardi; Nova Relida Samosir; Sabrina Hayati; Wahyu Margi Sidoretno (Syntax Literate, 2023)
Low back pain (LBP) is an uncomfortable sensation in the form of acute pain in the fifth lumbar vertebra and first sacrum (L5-S1). Half of the workers have complained of LBP, with a prevalence of LBP of 60-80%. Driving a vehicle can cause the back muscles to contract excessively, producing insufficient oxygen to support ATP production. The muscles then switch to anaerobic metabolism with the end product, lactic acid. The accumulated lactic acid then stimulates the nociceptors causing LBP. The existence of a daily achievement target system also causes drivers to insist on being able to complete many trips in one day, so drivers often ignore rest and working hours. The relationship between lactic acid levels and the incidence of low back pain in taxi drivers X Pekanbaru. This study used an observational analytic method, a cross-sectional, with the sampling technique used was total sampling, tested statistically using fisher exact. There is a relationship between lactic acid levels and the incidence of low back pain in taxi drivers X Pekanbaru (p-value = 0.000). Lactic acid levels are associated with low back pain in taxi drivers X Pekanbaru.